Innovation in the Development of Learning Media Management in the Context of Islamic Education at Santi Witya Serong School, Thailand - Setiawan, Hasrian Rudi; Wirian, Oktrigana; Wulandari, Ria (Yayasan Rahmat Islamiyah, 2025)
This study explores the innovation in developing learning media management within the context of Islamic education at Santi Witya Serong School, Thailand. The research emphasizes how effective management of instructional media can enhance the quality of teaching and learning, particularly in integrating Islamic values with modern educational practices. The study highlights the strategies applied in planning, organizing, implementing, and evaluating media usage to improve both teachers’ pedagogical skills and students’ learning outcomes. Findings indicate that innovative management practices contribute significantly to creating interactive, engaging, and contextually relevant learning environments. Moreover, the integration of technology-based media strengthens the effectiveness of Islamic education and aligns with the school’s vision to foster holistic development.